2022
DOI: 10.1001/jamanetworkopen.2022.10559
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of Serial Self-performed SARS-CoV-2 Rapid Antigen Detection Testing for Longitudinal Mass Screening in the Workplace

Abstract: Key Points Question Can untrained persons correctly perform and interpret the results of SARS-CoV-2 rapid antigen detection tests (RADT), and can performance be optimized? Findings In this cross-sectional study of 278 participants self-performing SARS-CoV-2 RADT in an intended-use setting, the accuracy of RADT interpretation was poor when the manufacturer’s instructions were used. A modified quick reference guide was associated with significantly better use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Of the 22 studies reviewed, 9 [ 11 , 12 , 13 , 14 , 18 , 25 , 35 , 37 , 39 ] used self-taken rapid antigen tests approved by the WHO for professional use [ 31 ], which are the STANDARD-Q COVID-19 Ag Test, Panbio COVID-19 Ag Rapid Test, LumiraDx SARS-CoV-2 Ag Test, Abbott Panbio COVID-19 Ag Rapid Test and SARS-CoV-2 Antigen Rapid Test (Flowflex).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 22 studies reviewed, 9 [ 11 , 12 , 13 , 14 , 18 , 25 , 35 , 37 , 39 ] used self-taken rapid antigen tests approved by the WHO for professional use [ 31 ], which are the STANDARD-Q COVID-19 Ag Test, Panbio COVID-19 Ag Rapid Test, LumiraDx SARS-CoV-2 Ag Test, Abbott Panbio COVID-19 Ag Rapid Test and SARS-CoV-2 Antigen Rapid Test (Flowflex).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the technique, the study of Tonen-Woleyc et al, 2021, revealed that the majority of participants (94.4%) understood the sample collection instructions [ 20 ], and in another study (Jing et al, 2022) 255 of 264 (96.6%) participants were able to perform the test successfully [ 42 ]. As a result, in many of these studies, the sensitivity and specificity were found to be the same between healthcare providers and non-healthcare providers [ 11 , 17 , 18 , 21 , 23 , 37 ]. Indeed, Savage et al, 2022, revealed that the sensitivity of self-taken rapid antigen tests was higher (90.5%) compared with professional-taken tests (78.3%) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CDC recently recommended continuation of wearing masks around others in public places until two consecutive negative RAT results ( 27 ). Taken together, RAT may detect replication-competent SARS-CoV-2 virus, and accuracy of this test can be improved by increasing the frequency or providing adequate guidance for procedure and interpretation ( 13 , 28 ). Our data on the daily RAT results provide important insights into the contingency or crisis plan during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent prospective study, we found that essential workers could perform self-testing adequately using manufacturer-included instructions, but that the interpretation of test results was significantly improved after modified instructions that emphasized key processes were implemented. 60 The cost of the tests themselves is about $5, 61 but other costs associated with testing are uncertain, and the need for RT-PCR confirmation will vary by epidemiologic setting and government policy.…”
Section: Discussionmentioning
confidence: 99%